Letter: low‐FODMAP diet for exercise‐induced gastrointestinal syndrome—Authors' reply. Issue 10 (20th October 2017) - Costa, R. J. S.; Snipe, R. M. J.; Kitic, C. M.; Gibson, P. R.
Abstract : Linked Content This article is linked to Uno and Costa et al papers. To view these articles visithttps://doi.org/10.1111/apt.14330 andhttps://doi.org/10.1111/apt.14157 .